Imam Al-Ghazali's Concept of Learning in Character Development Learners (Case Study In Madrasah Aliyah Student Dormitory Country 2 Malang) - A. Rosyid Sentosa; Raden Rizky Fahrial Ahmad; Muhammad Hamdani (Educan : Jurnal Pendidikan Islam, 2022)
This paper will discuss the effectiveness of the learning concept of Imam Al-Ghazali in developing the character of students at MAN 2 Malang. The concept of learning according to Imam Al-Ghazali himself is closely related to the relationship of human behavior, precisely human problems and education there is a very close relationship, and cannot be separated. In the world of education itself, there are two main goals, namely to give birth to a smart and intelligent generation, then the second to form a generation of humans who have good morals. But in many cases, there are many ways and shortcuts if you want to make your child smart. On the other hand, to form students who are moral, wise, and polite requires extra effort that is not instant. Several methods are needed that support and this is certainly not easy, it is quite difficult for educators to do. Thus, it is very reasonable to say that moral problems are acute problems or chronic diseases that accompany human life anytime and anywhere. Through the application of the right educational concept, Imam Al-Ghazali is able to provide a clearer picture of the character of students, which of course is accompanied by appropriate learning methods.